Demographics and inflation in the euro area: A two-sector new Keynesian perspective - Eliza Magdalena Lis; Christiane Nickel; Andrea Papetti (European Central Bank (ECB), 2020)
Can the aging process affect inflation? The prolonged decline of fertility and mortality rates induces a persistent downward pressure on the natural interest rate. If this development is not internalized by the monetary policy rule, inflation can be on a downward trend. Using the structure of a twosector overlapping generations model embedded in a New-Keynesian framework with price frictions, calibrated for the euro area, this paper shows that following a commonly specified monetary policy rule the economy features a "disinflationary bias" since 1990, in a way that can match the downward trend of core inflation found in the data for the euro area. In this model, continuing to follow the same rule makes inflation to be on a declining pattern at least until 2030. At the same time, changing consumption patterns towards nontradable items such as health-care generate a small "inflationary bias" a positive deviation of inflation from target of less than 0.1 percentage points between 1990 and 2030. In the model setting of this paper, this inflationary bias is not strong enough to counteract the disinflationary bias generated by the downward impact of aging on the natural interest rate.
Keywords: E43; E52; E58; J11; 330; population aging; monetary policy; inflation; euro area; consumption composition